Epistemology and methodology a reflextion upon unity, division, technology and knowledge (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The trial reflects on epistemology and methodology in economics, addressing the concepts of science, order division technology and knowledge. It has been used for the construction of the essay documentary research and critical reflection. This reflection comes from the recognition that the relationship between concepts from the epistemology of Economics is a non bias-free live field. It concludes briefly that the ideas, concepts and epistemas permeate in University systems when the conceptual frameworks are narrow and linear, and are limited to be considered equal to the term technical technology without taking into account the role of knowledge and the Organization and without considering that the technology is imbued with or embedded in the product. This way of thinking and rooting manifests itself in the processes of education and learning with the use of a paradigm that cleaves, creates the illusion of division and cracks the unity between subject and object. This is because of the epistemological development of the economic sciences when separating object from the subject, seeing technology as given.
Keywords: Epistemology; Methodology; Technology. Science; Order; Knowledge